2020
DOI: 10.3390/f11080796
|View full text |Cite
|
Sign up to set email alerts
|

The Organization of Nature Conservation in State-Owned Forests in Poland and Expectations of Polish Stakeholders

Abstract: Research Highlights: The presented findings result from the first large-scale research conducted in Poland in relation to the State Forests—the most important place for the protection of Polish nature. They may constitute an important contribution to the improvement of the nature conservation system. Background and Objectives: The current model of organization of nature conservation in the State Forests in Poland is not fully effective. In regard to the growing influence of society on nature protection and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Although the share of forest area administered by SF declined somewhat over the study period, it is still high, which is characteristic of the former socialist "Eastern Block" countries [1, 7,55]. In view of Poland's biodiversity conservation (all levels, including the landscape), state ownership of forests/lands constitutes a pillar of nature conservation [56]. Over the past years, forest expansion in Poland has slowed down as it has across Europe [1].…”
Section: Forest Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Although the share of forest area administered by SF declined somewhat over the study period, it is still high, which is characteristic of the former socialist "Eastern Block" countries [1, 7,55]. In view of Poland's biodiversity conservation (all levels, including the landscape), state ownership of forests/lands constitutes a pillar of nature conservation [56]. Over the past years, forest expansion in Poland has slowed down as it has across Europe [1].…”
Section: Forest Areamentioning
confidence: 99%
“…The majority of Poland's protected areas (excluding national parks) and objects are situated in forests under management of the State Forests (Table 3). At the beginning of 2019, in total 70.6% of the forests managed by SF were under different types of protection [56]. These were predominantly forested areas; however, there were also protected non-forest areas in spatial arrangements with forest areas (e.g., peatlands, water courses and reservoirs, heathlands).…”
Section: Dynamics Of Change Of Protected Forest Areamentioning
confidence: 99%
See 1 more Smart Citation
“…In close relation to engagement and empowerment, trust in specific entities and organizations is another important factor that needs to be taken into consideration. For example, in the study by Referowska-Chodak [18] in Poland, the authors found that levels of trust towards foresters were high, leading to a favorable opinion for this specific group to have a more leading role in nature conservation policies.…”
mentioning
confidence: 99%
“…However, poverty alleviation targets must not be completely ignored, as many West Africans rely on forest and catchment resources to support their livelihoods [19,22]. Finally, a common proposal in several papers of the SI, which brings us back to the second theme of the SI, is that forest conservation needs to become more inclusive and diverse by incorporating a number of local stakeholders in decision making processes [15][16][17][18].…”
mentioning
confidence: 99%